Multifunctional Train Ticket Service Terminal: Integration of Train Ticket Trading System with ATM for Enhanced Efficiency and Convenience (International Journal of Food and Nutritional Sciences, 2022)
This paper presents a novel approach to improve train ticket purchase services by integrating a train tickettrading system with an Automated Teller Machine (ATM) in an embedded mode. By combining an IC cardrecognition module and the ATM, the system achieves real-name system information checking, ensuring asecure and reliable user experience. Furthermore, the integration of a payment module with the ATMenables various payment modes, including cash and Unionpay transfer.